Efficacy of Continuous Femoral Nerve Block With Stimulating Catheters Versus Nonstimulating Catheters for Anterior Cruciate Ligament Reconstruction. Issue 4 (1st July 2007) - Dauri, Mario; Sidiropoulou, Tatiana; Fabbi, Eleonora; Giannelli, Marco; Faria, Skerdilajd; Mariani, Pierpaolo; Sabato, Alessandro Fabrizio
Abstract : Background and Objectives: This prospective randomized controlled trial investigated the clinical efficacy of stimulating catheters for continuous femoral nerve block in patients who underwent anterior cruciate ligament reconstruction. Methods: Seventy patients were randomized to either a stimulating catheter (SC, n = 35) or a nonstimulating catheter (NSC, n = 35) for femoral nerve block using 25 mL ropivacaine 7.5 mg/mL and clonidine 50 μg injected through the catheter. A single-injection sciatic block was also given to ensure surgical anesthesia. The time to loss of sensation to cold and pinprick of the femoral nerve was registered as the onset time. Data were registered intra- and postoperatively regarding pain scores, adverse effects, and need for supplemental anesthesia and analgesia other than a continuous postoperative infusion of ropivacaine 2 mg/mL through the continuous femoral nerve catheter set at 7 mL/h. Results: Onset time was faster in the SC group (SC: 6.4 ± 2.5, NSC: 8.3 ± 2.9 min, P = .006). Visual analog scale pain scores were similar in both groups. The number of patient-controlled regional analgesia boluses (SC: 14.6 ± 12.6, NSC: 23.2 ± 13.6 mg ropivacaine 2 mg/mL, P = .008) as well as intravenous rescue ketorolac (SC: 34.3 ± 35.7, NSC: 54 ± 39.7 mg, P = .033) administered were higher in the NSC group. Conclusion: Although the use of a stimulating catheter was associated with faster onset time for the femoral nerve block and lower additional analgesics postoperatively, the clinical superiority (analgesia; lateral femoral cutaneous, and obturator nerve block) of stimulating catheters was not evident in this clinical setting.